Gloss and surface analysis of various composite materials - Opačić-Galić Vanja; Popović Danica; Stašić Jovana N.; Dželetović Bojan; Manojlović Stefan (Serbian Medical Society - Dental Section, Belgrade, 2019)
Introduction To obtain the ideal aesthetics, each restorative material must imitate natural tooth in color, surface texture and be stable over time. Damage or wear of the material causes poor optical properties of the restoration, so it is necessary to repolish, repair or replace it. The aim of this study was to test the gloss and surface changes of the composite materials with filler's particles of different size, before and after material artificial mechanical ageing. Material and Methods Four composite materials were tested, two microhybrid composites (Gradia Direct GC, Herculite XRV, Kerr) and two nanohybrid composites (Filtek Ultimate 3M; TetricEvoceram, Ivoclar). Composites' samples of 9 × 9 × 2 mm in size were polished in accordance to the standard protocol by Sof-Lex discs (2382 C, SM, F, SF) for 30 seconds. Gloss was measured after polishing and taking photos using optical microscope (400×). In the chewing simulator, ageing of the samples was conducted (100,000 cyclic kicks). After the samples' ageing, surface photos were taken and gloss measured. The obtained results were statistically processed (One-way ANOVA, t-test). Results The best gloss after polishing was shown by Filtek Ultimate (54.00 ± 14.06), the worst by Gradia Direct (47.33 ± 7.92). There was no statistically significant difference (p > 0.05) in surface gloss after polishing composite. The smallest defects on the surface of composites were detected in material Gradia Direct (21363.7 mm2 ) with the average value of the diameter 137 mm. Conclusion The tested nanohybrid and microhybrid composites showed comparable gloss value before and after artificial aging. Mechanical aging caused vivid changes regarding surface defects on all tested composite materials.